2021
DOI: 10.1098/rsos.211606
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of T cells' antiviral and anti-inflammation immunities may be critical to death from COVID-19

Abstract: Clarifying dominant factors determining the immune heterogeneity from non-survivors to survivors is crucial for developing therapeutics and vaccines against COVID-19. The main difficulty is quantitatively analysing the multi-level clinical data, including viral dynamics, immune response and tissue damages. Here, we adopt a top-down modelling approach to quantify key functional aspects and their dynamical interplay in the battle between the virus and the immune system, yielding an accurate description of real-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Studies revealed that COVID-19 patients are characterized by dysregulated immune responses manifested as hyper-inflammatory immunological humoral reactions with the hallmark of cytokine storm (cytokine release syndrome); a life-threatening systemic inflammatory syndrome [3] , [4] . Besides, the cellular antiviral immune responses are impaired [5] . The molecular mechanisms behind dysregulated immune responses in COVID-19 patients are not well defined, and during viral infection, SARS-CoV-2 may also have developed various strategies to escape the host antiviral immune response and promote virus replication and disease progression [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that COVID-19 patients are characterized by dysregulated immune responses manifested as hyper-inflammatory immunological humoral reactions with the hallmark of cytokine storm (cytokine release syndrome); a life-threatening systemic inflammatory syndrome [3] , [4] . Besides, the cellular antiviral immune responses are impaired [5] . The molecular mechanisms behind dysregulated immune responses in COVID-19 patients are not well defined, and during viral infection, SARS-CoV-2 may also have developed various strategies to escape the host antiviral immune response and promote virus replication and disease progression [6] .…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 On the other hand, there is minimal induction of T cells in moderate to severe disease, 19 and an impairment in the T-cell response in death. 20 (However, some reports have observed opposite results: for example, higher activation of CD4 + and CD8 + T cells in severe disease; 21 also see below on conflicting evidence from studies on T-cell exhaustion.) A high level of Tregs (suppressive T-cell response) was associated with severe COVID.…”
Section: T-cell Control Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Thus, T cell response seems to develop early and correlate with protection, but it is relatively weakened in severe disease and is associated with intense activation and lymphopenia [ 15 ]. Although a high rate (up to 90%) of antibody seroconversion is detected among SARS-CoV-2-infected individuals 7–14 days post-symptom onset [ 16 , 17 ], the impairment of antiviral T cells functions is not compensated effectively by the increased antibody production and is considered as one of the main immunity-related causes of death from COVID-19 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%